Pemberdayaan Warga Griya Pataruman Asri Berbasis Urban Farming - Alviana, Sopian; Kurniawan, Bobi (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2023)
Community empowerment is one of the goals for citizens to actively participate in community activities. Limited agricultural land today, especially land in urban areas and housing - housing that has developed rapidly makes people have left agriculture. However, the need for agricultural products is still very high. Hydroponic Urban Farming is one form of urban farming by utilizing water for agriculture. In addition, the hydroponic concept does not require a very large area of land to grow crops. The purpose of community empowerment through this hydroponic urban farming scheme can be used as a utilization of vacant land to become a useful function change. In addition, this increases the understanding of residents to be able to utilize this very technology for agriculture with limited land. It is hoped that this Community Service scheme can provide training and understanding related to the utilization of current technology for limited agricultural land. The output of this program is in the form of providing hydroponic kits that can be used by residents to grow crops. This is intended to give residents the opportunity to try the process of planting with hydroponics. There were 10 hydroponic boxes given. Residents can take advantage to try planting with the given kit.